Physicochemical and organoleptic characteristics of dry noodle with the variation of addition of genjer leaf (Limnocharis flava) and spinach (Amaranthus hybridus L.) leaf as natural dye: Karakteristik fisikokimia dan organoleptik mi kering dengan variasi penambahan daun genjer (Limnocharis flava) dan daun bayam (Amaranthus hybridus L.) sebagai pewarna alami - Richo Fiariska Kurniawan; Nanik Suhartatik; Vivi Nuraini (Fakultas Sains dan Teknologi Unisri, 2025)
Dry noodles are one type of noodles in Indonesia. Noodles are a type of food that is low in protein and other nutrients, but high in carbohydrates. This is because the main ingredient in making noodles uses various types of flour, one of which is wheat flour. The purpose of this study was to ascertain the effect of adding genjer and spinach on the chemical and sensory qualities of dried noodles and to identify the optimal treatment combination in terms of nutritional value, antioxidant activity, and color that consumers like. The method used in this study was a completely randomized factorial design (CRD) in a two-factor variation with two repetitions, namely genjer puree concentrations of 10, 20 & 30% and spinach puree concentrations of 10, 20 & 30%. The results of the study found that the higher the concentration of genjer pulp, the higher the ash, protein, fiber, and total phenol content but not for the antioxidant activity. The addition of spinach puree apart from being a natural colorant can also help increase the fiber, ash, and antioxidant content of the noodles. Noodles had the best results of chemical analysis in the combination treatment of 20% genjer puree and 30% spinach puree with the results of 5.03% water content, 0.90% ash content, 12.12% protein, 9.93% fiber, 73.15% antioxidants, phenol 2.62 mgGAE/g. Dry noodles made from genjer and spinach have the potential to be developed because they have high antioxidant activity.